1996
DOI: 10.1093/treephys/16.3.381
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the photosynthetic capacity of Siberian and Japanese birch seedlings grown in elevated CO2 and temperature

Abstract: The effects of increased CO(2) and temperature on the photosynthetic capacity of Siberian white birch and Japanese white birch (Betula platyphylla Sukatch. and B. platyphylla Sukatch. var. japonica Hara) were measured. Birch seedlings were raised with a CO(2) partial pressure of 36 +/- 0.3 Pa (i.e., ambient) or 70 +/- 0.6 Pa at day/night temperatures of either 30/16 degrees C or 26/12 degrees C. Siberian birch leaves were smaller and thicker than Japanese birch leaves. Water use efficiency and nitrogen use eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 21 publications
4
18
0
1
Order By: Relevance
“…higher C-N ratios, accumulation of starch) (Koike et al, 1996;Tissue et al, 1999;Eguchi et al, 2004). However, birch and larch yielded no significant differences in methane emission between the elevated and the ambient [CO2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…higher C-N ratios, accumulation of starch) (Koike et al, 1996;Tissue et al, 1999;Eguchi et al, 2004). However, birch and larch yielded no significant differences in methane emission between the elevated and the ambient [CO2].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that plant leaves grown under high CO2 concentration ([CO2]) had different chemical and anatomical characters from those grown at ambient [CO2] (e.g. higher C-N ratios, accumulation of starch) (Koike et al, 1996;Tissue et al, 1999;Eguchi et al, 2004). We therefore expected that emission of methane from woody plants grown under elevated [CO2] would be greater than from those grown in ambient [CO2].…”
Section: Introductionmentioning
confidence: 99%
“…They called this phenomenon as photosynthetic adjustment or homeostatic adjustment in photosynthesis. Stimulation of photosynthesis by eCO 2 is observed during only a short period (the high photosynthetic rate is not maintained for a long period) and we regard this as down-regulation of photosynthesis (e.g., Coleman et al, 1993;Koike, 1993;Koike et al, 1996). Photosynthetic down regulation is considered to be due to: (1) rapid growth under eCO 2 with diluting nitrogen in the plant body, leading to nitrogen deficiency for growth (Coleman et al, 1993;Eguchi et al, 2008a) and temporal allocation to non-photosynthetic organs (Makino et al, 1997); (2) feedback regulation of Rubisco synthesis (e.g., Winter and Huber, 2000) or carbohydrate accumulation (Tissue et al 1997); and (3) sink-organ regulation (Usuda and Shimogawara, 1998) and accumulation of photosynthates in chloroplasts due to deficiency of inorganic phosphorus (Makino, 1994;Makino and Mae, 1999).…”
Section: Photosynthetic Adjustment and Tree Growthmentioning
confidence: 99%
“…Many studies using FACE or similar free air systems (e.g., Pepin and Körner, 2002;Onoda et al, 2005) suggest that stomatal conductance decreases in high CO 2 , and consequently WUE increases (e.g., Bazzaz, 1996;Koike et al, 1996;Saxe et al 1998;Körner et al, 2005;Nösberger, 2006;Wullschleger and Strahl, 2010). In our FACE studies, soil moisture conditions at eCO 2 remained relatively high in both soils (e.g., Eguchi et al, 2005;Kim et al, 2011).…”
Section: Water Relations and Wood Structurementioning
confidence: 99%
“…CO 2 는 광합성 과정을 통해 수목에 의 해 흡수된 후 탄수화물로 전환되어, 인간과 동물의 생존 에 필수적인 에너지로 제공된다 (Kim and Lee, 2001 Table 2. Summary of the effects of elevated atmospheric and meteorological variables on plants (Hawkins et al, 2008) 이 증가하는 긍정적인 효과를 나타내지만 (Ceulemans and Mousseau, 1994;Eamus and Berryman, 1995;Morison and Lawlor, 1999), 엽면적이 증가하면서 바람 에 대한 저항이 높아지고, 목재 품질이 감소하며, 영양 상 태가 불균형해지는 부정적인 효과도 함께 나타난다 (Koike et al, 1996). (Lemon, 1983;Long, 1991;Gifford, 1992;Bowes, 1996;Onoda et al, 2009 식물은 4%정도 상승할 것이라는 연구결과가 보고되었 다 (Kimball et al, 1993).…”
unclassified